2020
DOI: 10.1038/s41398-020-00967-3
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid, antineuronal autoantibody, EEG, and MRI findings from 992 patients with schizophreniform and affective psychosis

Abstract: The central role played by cerebrospinal-fluid (CSF) examinations including antineuronal autoantibody (Ab) testing is increasingly recognized in psychiatry. The rationale of this study was to present a multimodally investigated group of patients. In total, 992 patients were analyzed for CSF alterations: 456 patients with schizophreniform and 536 with affective syndromes. Ab measurement included testing for established antineuronal IgG-Abs against intracellular antigens in serum (Yo/Hu/Ri/cv2[CRMP5]/Ma1/Ma2/SOX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
60
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 47 publications
9
60
0
Order By: Relevance
“…In line with the aforementioned studies ( 19 , 23 ), we recommend immunotherapy ( Figure 1 and Table 1 ) for patients presenting probable or definitive autoimmune-based psychiatric syndromes according to this therapeutic pathway ( Figure 1 and Table 1 ): first-line immunotherapy should include steroids (i.v. or oral), IVIGs, immunoadsorption and/or PLEX.…”
Section: Autoantibody-associated Psychiatric Syndromes and Immunothermentioning
confidence: 70%
See 2 more Smart Citations
“…In line with the aforementioned studies ( 19 , 23 ), we recommend immunotherapy ( Figure 1 and Table 1 ) for patients presenting probable or definitive autoimmune-based psychiatric syndromes according to this therapeutic pathway ( Figure 1 and Table 1 ): first-line immunotherapy should include steroids (i.v. or oral), IVIGs, immunoadsorption and/or PLEX.…”
Section: Autoantibody-associated Psychiatric Syndromes and Immunothermentioning
confidence: 70%
“…Thirteen of 24 antibody-positive patients in this large cohort received immunotherapy, and 87% exhibited a good response to immunotherapy which had azathioprine, methotrexate, mycofenolat mofetil, and rituximab. Taken together, these large observational studies ( 19 , 23 ) deliver a low, but consistent evidence level that in those patients with psychiatric syndromes and proven autoantibodies, immunotherapy succeeded in 87–94% of patients ( n = 139). The evidence from these large retrospective case studies supports the usefulness of immunotherapy ( Table 1 ).…”
Section: Autoantibody-associated Psychiatric Syndromes and Immunothermentioning
confidence: 83%
See 1 more Smart Citation
“…The routine CSF analysis included the determination of white blood cell (WBC) count, protein concentration, AQ, immunoglobulin (Ig)G index, and oligoclonal bands (OCBs) according to an established methodology (c.f. Endres et al, 2015Endres et al, , 2020. The measurements were carried out in the CSF laboratory of the University Hospital Freiburg (https://www.uniklinikfreiburg.de/neurologie/klinik/diagnostische-einrichtungen/liquor-labor.html).…”
Section: Cerebrospinal Uid Analysis and Instrumental Diagnosticsmentioning
confidence: 99%
“…Schizophrenia spectrum disorders were interpreted by several authors as complex neuropsychiatric disorders involving an activated in ammatory response leading to mild neuroin ammation (Bechter, 2013;Muller, 2019;Müller et al, 2013;Nguyen et al, 2018;Stefanovic et al, 2016). In this context, the functions of the blood-brain barrier (BBB) and the blood-cerebrospinal uid (CSF) barrier (BCSFB) play a central role (Pollak et al, 2018), and a number of clinical studies showed alterations in biomarkers associated with the BBB/BCSFB (Endres et al, 2020;Endres et al, 2015;Najjar et al, 2017;Najjar et al, 2013;Orlovska-Waast et al, 2019). The central nervous system (CNS) is surrounded by the dynamic and metabolically active CSF and is separated from the peripheral circulation by several barriers, the most prominent are the BBB and the BCSFB (Banks et al, 2010;Deisenhammer et al, 2006;Tumani et al, 2017;Wildemann et al, 2010).…”
Section: Introductionmentioning
confidence: 99%